Analysis of the Background for the Failures of Poverty Alleviation Programmes Special Reference to Trincomalee District, Sri Lanka. - Sangjeli, Sothinathan; Mustafa, Abdul Majeed Mohamed (International Journal of Economics and Financial Issues, 2019)
Poverty is the major problem in the world. In fact, poverty is recognized as the main factor that influences the growth of economy in a country. Apparently, many regions still have the problem of poverty and make effort to reduce poverty. Consequently the scholars found the factors affecting poverty alleviation programmes are community participation, integrative framework, knowledge, stakeholder engagement, network, safety and security, redeployment, state of the programme, legislation and support, governance, political factors, corruption, lack of involvement, communication problems, problems of rural development programme, social sector and poverty, unemployment and the labor market, vulnerability of the poor, poor targeting. The government introduced many poverty alleviation programmes to eliminate the poverty but still the countries have the poverty. It means the programmes do not achieve the target. The independent variables are political factor, involvement, communication and knowledge. The primary data was collected from Divisional secretariats staffs who are directly involved in the poverty alleviation Programmes have considered for this research in the Trincomalee district. There are 11 divisional secretariats in the district. Therefore, 500 questionnaires issued to those divisions in the random sampling method. The analysis shows that political factors have a very strong correlation while communication and involvement has strong correlation. Moreover, knowledge has a negative correlation. Keywords: Poverty, Poverty Alleviation, Poverty Alleviation Programmes JEL Classifications: I32, I38 DOI: https://doi.org/10.32479/ijefi.8536